Availability of resources for paediatric hearing care in a South African province - Mukovhe Phanguphangu; Khomotjo Kgare; Ashley Flynn; Sinelihle Kotelana; Siphesihle Mfeketo; Sinovuyo Njiva (AOSIS, 2024)
Background: Unavailability of healthcare resources can lead to poor patient outcomes. The latter is true for infants with hearing loss and require early hearing detection and intervention (EHDI). Aim: To determine the availability and distribution of resources for EHDI in state hospitals in the Eastern Cape (EC) province, South Africa. Setting: Sixteen state hospitals (nine district, four regional and three tertiary hospitals). Methods: Descriptive cross-sectional survey completed between July 2022 and October 2022. Results: Thirteen hospitals had audiologists (n = 4) or speech therapists and audiologists (n = 9). Specific to equipment, 10 hospitals had a screening otoacoustic emissions or automated auditory brainstem response, 8 hospitals had diagnostic middle ear analysers and only 3 hospitals had diagnostic auditory brainstem response and/or auditory steady state response. Twelve hospitals did not have visual response audiometry (VRA) and 94% had no hearing aid verification systems. Budget allocations were uneven, with only 10 hospitals, i.e., 4 districts, all regional and 2 tertiary hospitals being allocated varying amounts. Subsequently, only 50% provided newborn hearing screening, 56% provided diagnostic evaluations and 14 hospitals fitted hearing aids. Conclusion: Results revealed a limited and uneven distribution of resources, which negatively impacted the provision of EHDI. Even distribution of healthcare resources and further research aimed at strengthening hearing health services is recommended as these could potentially improve equitable access to EHDI and the overall quality of healthcare provided. Contribution: This study highlights the need for even distribution of resources and strengthening of health systems, especially in the dawn of the National Health Insurance.